2014
DOI: 10.46989/001c.20784
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Feed Utilization by Golden Grey Mullet (Liza aurata) in a Coastal Lagoon Ecosystem, Fed Compound Feeds with Varying Protein Levels

Abstract: As from January 2010 The Israeli Journal of Aquaculture -Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions.This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…It is reported that in 5 month culture lesser mullets attained a lower growth rate, 0.28 to 0.35 g DWG and 0.40 to 0.48% per day SGR compared with fast growing M. cephalus (Karapanagiotidis et al, 2004). However, in the present study L. parsia and L. tade recorded better growth performance (Table 3) compared with earlier observation (Biswas, Ananda Raja, et al, 2012;James, 1996;Shofiquzzoha et al, 2001).…”
Section: Economic Analysiscontrasting
confidence: 63%
See 1 more Smart Citation
“…It is reported that in 5 month culture lesser mullets attained a lower growth rate, 0.28 to 0.35 g DWG and 0.40 to 0.48% per day SGR compared with fast growing M. cephalus (Karapanagiotidis et al, 2004). However, in the present study L. parsia and L. tade recorded better growth performance (Table 3) compared with earlier observation (Biswas, Ananda Raja, et al, 2012;James, 1996;Shofiquzzoha et al, 2001).…”
Section: Economic Analysiscontrasting
confidence: 63%
“…Moreover, the residues of macrobenthos, fish or molluscan meal fed by mudcrabs also might have served as food for bottom detritus feeder grey mullet compared with plankton feeding milkfish. It is reported that in 5 month culture lesser mullets attained a lower growth rate, 0.28 to 0.35 g DWG and 0.40 to 0.48% per day SGR compared with fast growing M. cephalus (Karapanagiotidis et al., ). However, in the present study L. parsia and L. tade recorded better growth performance (Table ) compared with earlier observation (Biswas, Ananda Raja, et al., ; James, ; Shofiquzzoha et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the growth rates of M. cephalus were relatively low at the end of the 28-week feeding period, they were comparable to those reported in previous studies carried out with this and other similar species that evidence the slow growth rate of mugilids [29][30][31]. Legarda et al [32] reported an SGR of 0.56%/day for Mugil cephalus juveniles fed 1%bw daily in a biofloc system maintained at 28 ± 1 • C. Nengas et al [33] also recorded low SGR values (around 0.45%/day) in juveniles of Liza aurata fed once per day at 2% of their biomass at temperatures ranging from 12 to 26 • C.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it must be considered that the conditions in which the fish were maintained in this latter experiment, mainly a lower stocking density, could result in lower stress and a positive impact on feeding behaviour, resulting in better food utilization. Although there are few studies on the nutrition of mullets under field conditions, the study carried out by [33] on Liza aurata showed that growth and feed utilization of the fish was not significantly affected by variations in the dietary protein level. Such absence of a clear effect could be due to the possible complementary effect of natural food present in the water mass.…”
Section: Discussionmentioning
confidence: 99%